(untitled) (Journal of the College of Basic Education, 2025)
Athletics is one of the most important sports that rely on the elements of fitness and specific physical fitness capabilities. As a result, the long jump is an event that requires a high integration of strength, speed, and technical skills. A special element of physical strength is prominent in it as a powerful factor in achieving outstanding accomplishments. Advanced strength is defined as the ability to produce maximum force in the shortest possible time. It represents empirical evidence of the decisive role played in the advancement phase through the technical performance of the long jump. From here, this type of strength develops and moves from its initial stages to its current level, especially in youth, which is a long period of athletic development. Numerous studies have proven that the use of multiple programs for digital jumping and loads contributes to improving physical fitness and explosiveness, leading to improved performance in the events that rely on it. Therefore, this aims to research a training program using strong power development and the extent of its reflection on improving the digital level of long jumpers from the youth category as well as sports to provide general views on the effectiveness of this publication of programs, then in the preparations for the specialist in athletics, the experimental game was used from the group design, Brent on a fully. intentional creative (20) competitors, and the program was applied using training exercises for a period of (6) weeks at a rate of three copies per week for a total of (18) units. To measure the program after using the set of fluidity necessary for achievement, which are: (long jump from a standstill, throwing the medicine ball weighing 2 kg from above the head to the farthest distance), the researchers succeeded in testing the proficient levels of digital achievement for the effectiveness of the long jump, and the results showed that there is a positive effect